Investigating the effect of chain writing method on students’ writing skills in a junior secondary school - Puspitasari, Neta; Kusumawanti, Windhariyati Dyah (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
This research aims to examine the effect of chain writing method on students’ writing skills in a junior high school situated in Banyumas, Central Java Province, Indonesia. This study was designed with quasi-experimental research since the research sample was determined employing random sampling technique. The population of this research was 256 students of the eighth grade in the junior secondary school. Data were garnered used pre-test and post-test after giving a treatment. The data were analyzed using normality test, homogeneity test, and hypothesis test. Based on the hypothesis test, the significance level was < 0.05. In this research the Sig. 2-tailed was 0.000. The Sig. 2 tailed 0.000 < 0.05. Study results demonstrate that there was a significant effect of the chain writing method application on the students’ writing skills. The statistical attainment indicated that H0 was rejected, and Ha was accepted. This study concludes with pedagogical implications for how chain writing can be applied as an innovative teaching method for teaching writing, particularly for secondary school students.